Vaginal Microbiota, Genital Inflammation and Extracellular Matrix Remodelling Collagenase: MMP-9 in Pregnant Women With HIV, a Potential Preterm Birth Mechanism Warranting Further Exploration - Short, Charlotte-Eve S.; Quinlan, Rachael A.; Wang, Xuan; Preda, Veronica Georgiana; Smith, Ann; Marchesi, Julian R.; Lee, Yooni S.; MacIntyre, David A.; Bennett, Phillip R.; Taylor, Graham P. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Pregnant women living with HIV infection (PWLWH) have elevated rates of preterm birth (PTB) in which HIV and cART are implicated. PWLWH also have a high prevalence of adverse vaginal microbiota, which associate with genital tract inflammation. The mechanism underlying PTB in PWLWH is unknown. We present the first data in PWLWH on genital-tract matrix-metalloproteinase-9(MMP-9), an important collagenase implicated in labour onset, and tissue inhibitor of metalloproteinases-1(TIMP-1) and explore correlations with local inflammation and vaginal bacteria. Material and Methods Cervical vaginal fluid (CVF) collected by a soft cup and high vaginal swabs (HVS) were obtained from PWLWH and HIV uninfected pregnant women (HUPW) at three antenatal time points. Maternal characteristics, combination antiretroviral therapy (cART) exposure, and pregnancy outcome were recorded. Concentrations of MMP-9, TIMP-1 and ten cytokines were measured by immunoassays. Vaginal microbiota composition was determined through 16S rRNA amplicon sequencing. MMP-9, TIMP-1 and cytokine concentrations were compared by HIV status, cART, and prematurity and in PWLWH correlations with polymorphonuclear leucocytes, cytokines and bacterial genera were explored. Results CVF was available for 50 PWLWH (108 samples) and 12 HUPW (20 samples) between gestation weeks 14-38. Thirty-six PWLWH conceived on cART and 14 initiated post-conception. There were five and one PTB outcomes in PWLWH and HUPW respectively. PWLWH had higher mean CVF concentrations of MMP-9 (p<0.001) and TIMP-1 (p=0.035) in the second trimester compared with HUPW with a similar trend in the third trimester. PWLWH also had higher CVF values of cytokines: IL-1β, IL-8, IL-12 and TNF-α in both trimesters compared to HUPW (p ≤ 0.003). In PWLWH, MMP-9 positively correlated with TIMP-1 (r=0.31, p=0.002) and CVF polymorphonuclear leucocytes (r=0.57, p=0.02). Correlations were observed between MMP-9 and three cytokines: IL-1β (r=0.61), IL-8 (r=0.57) and TNF-α (r=0.64), p<0.001, similarly for TIMP-1. Abundance of anaerobic pathobionts correlated with MMP-9: Gardnerella (r=0.44, p<0.001), Atopobium (r=0.33, p=0.005), and Prevotella genera (r=0.39, p<0.001). Conversely proportion of Lactobacillus genera negatively correlated with MMP-9 (rho=-0.46, p<0.001). MMP-9/TIMP-1 ratio increased with gestational age at sampling in PWLWH, but this was no longer significant after adjusting for confounders and no difference by prematurity was observed in this sub-study. Conclusions Here we show strong correlations of MMP-9 to genital tract inflammation and sub-optimal bacterial genera in PWLWH indicating the ascending genital tract infection pathway may be a contributory mechanism to the high risk of PTB.